Non-ICT teachers' strategies in informatics teaching under Kurikulum Merdeka challenges - Cikal Kautsar Qadri (Hipkin Journal of Educational Research, 2026)
Computer science education aims not only to equip students with technical skills but also to foster logical, systematic, and creative thinking. However, it is often found that teachers lack a background in Information and Communication Technology (ICT). This study examines the pedagogical and technological challenges faced by non-ICT teachers in implementing the Computer Science subject under the Kurikulum Merdeka at SMA Kartika XIX-2 Bandung. Using a descriptive qualitative approach, data were collected through semi-structured interviews conducted in two sessions. This study found that Computer Science teachers face significant barriers, particularly regarding infrastructure and institutional support. The main barriers identified include limited infrastructure, a lack of pedagogical and technical training, and difficulties in adapting teaching materials such as Alur Tujuan Pembelajaran (ATP) and modules. To address these challenges, teachers implemented adaptive strategies through self-directed learning, informal mentoring with peers, and online digital learning resources. These strategies reflect pedagogical flexibility and a spirit of innovation that enable learning to continue despite limitations.   Abstrak Pembelajaran Informatika tidak hanya bertujuan membekali murid dengan keterampilan teknis, tetapi juga membentuk pola pikir logis, sistematis, dan kreatif. Namun, sering kali ditemukan guru yang tidak berlatar pendidikan Teknologi Informasi dan Komunikasi (TIK). Penelitian ini mengkaji tantangan pedagogis dan teknologi yang dihadapi oleh guru berlatar belakang non-TIK dalam pelaksanaan mata pelajaran Informatika pada Kurikulum Merdeka di SMA Kartika XIX-2 Bandung. Melalui pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara semi-terstruktur dalam dua sesi. Penelitian ini menemukan bahwa guru mata pelajaran Informatika menghadapi hambatan signifikan, terutama pada aspek infrastruktur dan dukungan kelembagaan. Hambatan utama yang ditemukan meliputi keterbatasan infrastruktur, minimnya pelatihan pedagogis dan teknis, serta kesulitan dalam menyesuaikan perangkat ajar seperti Alat Tujuan Pembelajaran (ATP) dan modul. Dalam mengatasi tantangan tersebut, guru menerapkan strategi adaptif melalui pembelajaran mandiri, mentoring informal dengan sejawat, dan sumber belajar digital daring. Strategi ini mencerminkan fleksibilitas pedagogis dan semangat inovasi yang memungkinkan pembelajaran tetap berjalan meski dalam keterbatasan. Kata Kunci: guru non-TIK; Kurikulum Merdeka; teknologi informasi dan komunikasi